Development of the composition and technology of an alcohol-free hand sanitiser - Tarasenko, Hanna; Saliy, Olena; Muravskyi, Bohdan; Popova, Maria; Kuzmina, Galyna (Technologies and Engineering, 2026)
Effective hand hygiene is a key factor in the prevention of infectious diseases, which creates a need for safe and highly effective antiseptic products and underscores the relevance of developing formulations with optimal antimicrobial, dermatological, and technological properties. The objective of the study was to develop an alcohol- free hand antiseptic with high antimicrobial activity, skin safety, and compatibility with sensor-based dispensers. The analysis of the hand antiseptic market was conducted using analytical and statistical methods, while the determination of quality parameters of the hand antiseptic was carried out using organoleptic, physicochemical, and microbiological control methods. It was established that alcohol-based products – ethanol, propanol, and isopropanol – dominate the antiseptic market (over 70%), and their main limitations were identified, including the potential to cause skin dryness, risk of irritation with prolonged use, and increased flammability. Based on the conducted analysis, an alcohol-free composition was proposed, in which benzalkonium chloride (0.1-0.15%) was identified as the optimal active ingredient. Four formulation variants with different essential oils were studied; it was determined that the samples had a pH ranging from 4.8 to 5.3 and a viscosity of 22-24 mPa·s. The sample containing demonstrated the best overall parameters, with a pH of 5.3 ± 0.2, viscosity of 23 ± 0.3 mPa·s, transparency and stability, as well as improved organoleptic properties. All samples met microbiological requirements, and the content of benzalkonium chloride was 0.12 ± 0.02%, confirming accurate dosing. A technological process for obtaining the antiseptic through the preparation of two phases followed by their combination was proposed, ensuring the stability and homogeneity of the final product. The results of this study can be utilised by manufacturers of cosmetic and disinfectant products to create alcohol-free hand antiseptics suitable for use in medical, educational, and social institutions, as well as in household settings, including applications with sensor-based hand sanitiser dispensers.